Variation and evolution analysis of SARS-CoV-2 using self-game sequence optimization - Liu, Ziyu; Shen, Yi; Jiang, Yunliang; Zhu, Hancan; Hu, Hailong; Kang, Yanlei; Chen, Ming; Li, Zhong (Frontiers in Microbiology, 2024)
IntroductionThe evolution of SARS-CoV-2 has precipitated the emergence of new mutant strains, some exhibiting enhanced transmissibility and immune evasion capabilities, thus escalating the infection risk and diminishing vaccine efficacy. Given the continuous impact of SARS-CoV-2 mutations on global public health, the economy, and society, a profound comprehension of potential variations is crucial to effectively mitigate the impact of viral evolution. Yet, this task still faces considerable challenges.MethodsThis study introduces DARSEP, a method based on Deep learning Associates with Reinforcement learning for SARS-CoV-2 Evolution Prediction, combined with self-game sequence optimization and RetNet-based model.ResultsDARSEP accurately predicts evolutionary sequences and investigates the virus’s evolutionary trajectory. It filters spike protein sequences with optimal fitness values from an extensive mutation space, selectively identifies those with a higher likelihood of evading immune detection, and devises a superior evolutionary analysis model for SARS-CoV-2 spike protein sequences. Comprehensive downstream task evaluations corroborate the model’s efficacy in predicting potential mutation sites, elucidating SARS-CoV-2’s evolutionary direction, and analyzing the development trends of Omicron variant strains through semantic changes.ConclusionOverall, DARSEP enriches our understanding of the dynamic evolution of SARS-CoV-2 and provides robust support for addressing present and future epidemic challenges.